A Comparative Study of Physicochemical Attributes of Pigmented Landrace Maize Varieties. (2nd November 2022) - Majamanda, James; Katundu, Mangani; Ndolo, Victoria; Tembo, David
Abstract : Maize has been cultivated and continues to be cultivated for its usability in calorie supply to humans and livestock. There has been great interest in pigmented landrace maize varieties (PLMVs) due to their importance in the pharmaceutical industry. Landraces are to a large extent a repository of the gene pool that enriches biodiversity and maintains but also stabilizes the ecosystem in a sustainable way. PLMVs are still being cultivated by smallholder farmers in smaller portions of their fields and home surroundings despite the high adoption of white hybrid maize. This study examined the ash, moisture, mineral, crude protein, fat, and carbohydrate content of three different PLMVs from central (Ntcheu and Dedza districts) and northern (Mzimba district) Malawi. The mineral content of soils from fields where PLMVs were grown was also analyzed. The study areas experience a warm temperate climate and higher rainfall in summer than in winter but they differ in that Ntcheu has the highest average annual temperature of 20.3°C while Dedza receives the highest annual precipitation of about 1010 mm. Mzimba's average annual temperature and precipitation are 20.1°C and 915 mm, respectively. The study showed that orange maize from Dedza had a significantly higher content of calcium (71.00 ± 0.58 mg·kg −1 ), magnesium (819.00 ± 0.58 mg·kg −1 ), and phosphorus (2720.35 ± 0.03 mg·kg −1 ). Significantly higher contents of zinc (54.61 ± 0.43 mg·kg −1 ) and potassium (808.58 ± 0.27 mg·kg −1 ) were observed in purple maize from Dedza and Ntcheu, respectively. Red maize from Dedza had a significantly higher content of iron (59.80 ± 0.26 mg·kg −1 ). Purple maize from Dedza has significantly higher carbohydrate content (65.52 ± 0.07%). The findings also revealed that red maize from Dedza provenance had a high content of crude protein (12.57 ± 0.07%) and fat (10.73 ± 0.14%). Moisture (17.30 ± 0.21%) and ash (2.28 ± 0.02%) were significantly higher in orange maize from Dedza. Dedza's provenance revealed a high content of the analyzed attributes in PLMVs. Mineral analysis showed different levels of mineral bioavailability in different PLMVs and in the soils where maize was grown. It can, therefore, be concluded that production location and maize variety have an influence on the attributes of PLMVs. Understanding the physicochemical attributes of PLMVs and its maximum utilization have the potential of improving food and nutrition security in Sub-Saharan African countries and globally.